2004
DOI: 10.1152/ajpcell.00111.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone treatment causes resistance to insulin-stimulated cellular potassium uptake in the rat

Abstract: Patients treated with glucocorticoids have elevated skeletal muscle ouabain binding sites. The major Na(+)-K(+)-ATPase (NKA) isoform proteins found in muscle, alpha2 and beta1, are increased by 50% in rats treated for 14 days with the synthetic glucocorticoid dexamethasone (DEX). This study addressed whether the DEX-induced increase in the muscle NKA pool leads to increased insulin-stimulated cellular K+ uptake that could precipitate hypokalemia. Rats were treated with DEX or vehicle via osmotic minipumps at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Bound antibody was visualized by labeling with an Alexa Fluor-conjugated anti-rabbit or anti-mouse antibody (Molecular Probes). Mouse monoclonal antibodies against the ␣3 Na,K-ATPase (XVIF9-G10, Research Diagnostics, Inc. (18)) and ␣1 Na,K-ATPase (clone 9A-5; A275, SigmaAldrich (19)) and rabbit serum against the ␣2 Na,K-ATPase (AB9094, Millipore (20,21)) were used at a dilution of 1:200. R␣Ag-1, a pan-specific rabbit anti-agrin serum (22) was used at a dilution of 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…Bound antibody was visualized by labeling with an Alexa Fluor-conjugated anti-rabbit or anti-mouse antibody (Molecular Probes). Mouse monoclonal antibodies against the ␣3 Na,K-ATPase (XVIF9-G10, Research Diagnostics, Inc. (18)) and ␣1 Na,K-ATPase (clone 9A-5; A275, SigmaAldrich (19)) and rabbit serum against the ␣2 Na,K-ATPase (AB9094, Millipore (20,21)) were used at a dilution of 1:200. R␣Ag-1, a pan-specific rabbit anti-agrin serum (22) was used at a dilution of 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, its chronic use leads to several side eVects, such as alterations in sugar, lipid and protein metabolism, which may result in diabetes, dyslipidemic disease, hypertension and metabolic syndrome. Chronic glucocorticoid treatment may also result in insulin resistance followed by hyperinsulinemia and hyperglycemia, (Weinstein et al 1995;Qi et al 2004;Rhee et al 2004;Brotman et al 2005;Patel et al 2006;Coderre et al 2007). These alterations of insulin and glucose levels could be partially explained by impairment of insulin signaling in hepatic and extra hepatic (muscle and fat) tissues (Saad 1994;Andrews and Walker 1999;Brown et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been observed that a dose-dependent reduction of body weight occurs in animals treated with glucocorticoids (De Vries et al 2002;Komamura et al 2003;Ahtikoski et al 2004;Rhee et al 2004;Coderre et al 2007;Kaasik et al 2007;Menezes et al 2007). This weight loss is usually followed by muscle atrophy and a reduction of several muscle proteins, contributing to impaired muscle function (De Vries et al 2002;Komamura et al 2003;Ahtikoski et al 2004;Lumbers et al 2005;Gilson et al 2007;Kaasik et al 2007;Menezes et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hormonal induction of Na ϩ -K ϩ -ATPase subunit expression may be subunit specific, as evidenced by the selective upregulation of ␣ 2 and ␤ 1 mRNA and protein expression shown by analysis of ␣ 1 , ␣ 2 , ␤ 1 , and ␤ 2 expression in rat skeletal muscle after treatment with the artificial glucocorticoid dexamethasone (46). Furthermore, treatment with dexamethasone has been shown to result in a dose-dependent increase in [ 3 H]ouabain binding sites in rat skeletal muscle (10,39), confirming that changes at the mRNA level are likely to cause changes in Na ϩ -K ϩ -ATPase protein expression. Plasma levels of thyroid hormone do not change with exercise (13,43), but both cortisol (5,47,48) and GH (14) increase during and after exercise.…”
mentioning
confidence: 99%